Significant continental source of ice-nucleating particles at the tip of Chile's southernmost Patagonia region - Gong, Xianda; Radenz, Martin; Wex, Heike; Seifert, Patric; Ataei, Farnoush; Henning, Silvia; Baars, Holger; Barja Gonzalez, Boris; Ansmann, Albert; Stratmann, Frank (My University, 2022)
The sources and abundance of ice-nucleating particles (INPs) that initiate cloud ice formation remain understudied, especially in the Southern Hemisphere. In this study, we present INP measurements taken close to Punta Arenas, Chile, at the southernmost tip of South America from May 2019 to March 2020, during the Dynamics, Aerosol, Cloud, And Precipitation Observations in the Pristine Environment of the Southern Ocean (DACAPO-PESO) campaign. The highest ice nucleation temperature was observed at -3 degrees C, and from this temperature down to similar to 10 degrees C, a sharp increase of INP number concentration (N-INP) was observed. Heating of the samples revealed that roughly 90% and 80% of INPs are proteinaceous-based biogenic particles at > -10 and -15 degrees C, respectively. The N-INP at Punta Arenas is much higher than that in the Southern Ocean, but it is comparable with an agricultural area in Argentina and forestry environment in the US. Ice active surface site density (n(s)) is much higher than that for marine aerosol in the Southern Ocean, but comparable to English fertile soil dust. Parameterization based on particle number concentration in the size range larger than 500 nm (N->500 nm) from the global average (DeMott et al., 2010) overestimates the measured INP, but the parameterization representing biological particles from a forestry environment (Tobo et al., 2013) yields N-INP comparable to this study. No clear seasonal variation of N-INP was observed. High precipitation is one of the most important meteorological parameters to enhance the N-INP in both cold and warm seasons. A comparison of data from in situ and lidar measurements showed good agreement for concentrations of large aerosol particles (> 500 nm) when assuming continental conditions for retrieval of the lidar data, suggesting that these particles were well mixed within the planetary boundary layer (PBL). This corroborates the continental origin of these particles, consistent with the results from our INP source analysis. Overall, we suggest that a high N-INP of biogenic INPs originated from terrestrial sources and were added to the marine air masses during the overflow of a maximum of roughly 150 km of land before arriving at the measurement station.
Keywords: Ice nucleus; Particle (ecology); Ice core